Design Smart Installation Household Electricity Using Solar Panels 600 Watts on Grid Capacity - Nasution, Rahmatsyah Handayani Ramadhan; Salsabilla, Annisa; Ridho’i, M. Fachmi; Murniati, Riri (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2024)
Energy security plays an important role, especially in the modern and digital era which continues to increase in use. The availability of renewable energy sources is very abundant in tropical countries of Indonesia, especially solar energy sources that can be used to meet electricity needs on a household scale without worrying about limitations and pollution. This study aims to design electrical installations using solar panels with an autonomous drive system following Arduino uno-based sunlight with a capacity of 600 watts on-grid to reduce the cost burden of PLN and reduce air pollution. The addition of Arduino uno autonomous devices plays a role in increasing the efficiency of solar radiation received thereby increasing the output power of the installation. The result of this study is the design of a power plant installation with a solar cell with a capacity of 600 watts with 13 50-watt monocrystalline PV solar modules with supporting components, such as a 1000-watt inverter, and an efficiency device in the form of an Arduino uno-based autonomous drive system. This research produces data on the benefits obtained by using this tool amounting to Rp. 12.500 / month for 20 years of efficiency in using solar panels.